2020
DOI: 10.3390/f11090950
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Atmospheric Suspended Particulate Matter Concentration and Influencing Factors of Green Space in Urban Forest Park

Abstract: In the process of urbanization in China, the problem of atmospheric suspended particulate matter pollution is becoming increasingly serious. It has been impossible to completely rely on pollution source control measures to solve this problem for a long time due to the diversity and complexity of pollution sources. Therefore, there is an urgent need to explore alternate solutions to significantly improve air quality through increasing the capacity of green space in cities as these locations can provide multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…As Riondato, et al [22] declared, vegetated areas can filter pollutants and effectively reduce PM concentrations. This is in accord with other studies which, in particular, examined leaf characteristics (e.g., cuticle chemical composition [23] and the wax layer [24]), tree canopy size, plant health condition [25], groove and trichome distribution [26], PM deposition velocity, the ground surface fraction of vegetation [27], and tree and shrub density [28]. Finally, barren deserts, in particular when subjected to high-speed wind capable of blowing dust and sand, can act as sources of PM [29].…”
Section: Pm Urban Form and Landscape Ecologysupporting
confidence: 91%
See 1 more Smart Citation
“…As Riondato, et al [22] declared, vegetated areas can filter pollutants and effectively reduce PM concentrations. This is in accord with other studies which, in particular, examined leaf characteristics (e.g., cuticle chemical composition [23] and the wax layer [24]), tree canopy size, plant health condition [25], groove and trichome distribution [26], PM deposition velocity, the ground surface fraction of vegetation [27], and tree and shrub density [28]. Finally, barren deserts, in particular when subjected to high-speed wind capable of blowing dust and sand, can act as sources of PM [29].…”
Section: Pm Urban Form and Landscape Ecologysupporting
confidence: 91%
“…This is possibly due to a relatively high land roughness related to the contiguous edges of the forest, such as the fortress form, which would help capture airborne pollutants more efficiently [ 45 ]. It is also well known that a high density of leaves and canopy could block and rub the particles and that the sedimentation process would be accelerated in forests [ 28 ]. On the contrary, different types of urban structures with different sizes, heights, and shapes in developed areas—where land cover data cannot be directly measured through satellite images—may decrease the ventilation ability [ 39 ] and act as wind barriers [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to represent the monthly PM concentration because PM measurement was carried out during just 1 day. However, we identified days with monthly weather characteristics in advance, and previous studies also showed monthly PM concentrations as a result of measuring PM for a short time [24,29]. So, we can speculate that our measuring data can show the feature of monthly PM.…”
Section: Pm Measurement At Human Breathing Heightmentioning
confidence: 84%
“…Due to the importance of health problems caused by atmo-spheric contaminants and the increase in the number of citizens living in megacities, there is a growing interest in the utilization of green elements for contaminant dissipation. Several studies have demonstrated that the surface with green-coverage is inversely correlated with the amount of PM contamination in the air, although the type of green coverage is also important [205,[224][225][226].…”
Section: Removal Of Air Pollutants and The Role Of Green Architecturementioning
confidence: 99%